2012
DOI: 10.1021/pr3000317
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomics Reveals Plasma Metabolic Changes and Inflammatory Marker in Polycystic Ovary Syndrome Patients

Abstract: Polycystic ovary syndrome (PCOS) is a common, clinically heterogeneous endocrine disorder affecting women of reproductive age, associated with endocrinopathy and metabolic abnormalities. Although some metabolic parameters have been investigated, very little information has been reported on the changes of small metabolites in biofluids. The aim of this study was to establish the metabolic profile of PCOS and compare it with that of controls. In this cross-sectional study of 34 women with PCOS and 36 controls, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
104
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 73 publications
9
104
2
1
Order By: Relevance
“…N-acetylglycoprotein (NAG) is an acute-phase response protein in response to many cytokines derived from inflammatory cells such as neutrophils and macrophages, and it was used as inflammation marker in previous study [30]. In this study, we observed increased serum NAG in DN rats, suggesting the enhanced inflammatory responses during the Fig.…”
Section: Discussionsupporting
confidence: 48%
“…N-acetylglycoprotein (NAG) is an acute-phase response protein in response to many cytokines derived from inflammatory cells such as neutrophils and macrophages, and it was used as inflammation marker in previous study [30]. In this study, we observed increased serum NAG in DN rats, suggesting the enhanced inflammatory responses during the Fig.…”
Section: Discussionsupporting
confidence: 48%
“…Following cellular uptake, uridine is converted to UTP, which can then be utilized for the synthesis of RNA, phosphocholine (Cansev et al 2008) or glycogen via glycogenesis. The concomitant increase in the concentration of N-acetyl groups, which are associated with glycoproteins, glycolipids and important antioxidant constituents, may be indicative of a follicular environment that was more sensitive to oxidative stress and/or increased inflammation and cell damage (Kolwijck et al 2009, Sun et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…The currently available metabolomic technologies allow for comprehensive metabolic profiling and may represent a large step toward understanding the pathogenesis of PCOS. Metabolomic studies of PCOS samples have been performed by analyzing plasma samples using either hydrogen-1 nuclear magnetic resonance ( 1 H NMR) [3,4], gas chromatography-tandem mass spectrometry (GC-MS) [5] or 1 H NMR combined with GC-MS [6]. The altered metabolites were observed to be mostly involved in the metabolism of carbohydrates, lipids and amino acids.…”
Section: Introductionmentioning
confidence: 99%